The Effectiveness of Expressive Writing Therapy on Anxiety Levels in School-Age Children Undergoing Hospitalization - Tody, Selvin; Simanjuntak, Susi Roida; Babakal, Abram (Inspirasi Foundation, 2024)
Introduction: Anxiety disorders are one of the psychological problems that arise when children undergo hospitalization. Anxiety that is not treated will make the length of hospitalization days and worsen conditions. One of the interventions that can be done to treat anxiety in school-age children undergoing hospitalization is expressive writing therapy. Objective: This study aims to determine the effectiveness of expressive writing therapy on the anxiety of school-age children undergoing hospitalization. Methods: This research design uses quantitative methods with a pre-experimental one group pretest-posttest design. The study sample consisted of 25 respondents selected using purposive sampling technique based on the inclusion criteria, namely school-age children aged 10-12 years who can write, children who are undergoing hospitalization with stable conditions (children who are willing to communicate well and are able to sit on the patient's bed, parents who are willing for their children to become respondents, and children who experience anxiety based on screening results. Anxiety was measured using an instrument (CSAS-C). Results: Data analysis with the Paired Sample t-test test showed a p value = 0.000 (p <0.05) which means there is a difference in the average score of anxiety before and after the expressive writing therapy intervention. Conclusion: Based on the results of the analysis, it can be concluded that there is an effect of expressive writing therapy intervention on the average difference in anxiety of school-age children undergoing hospitalization before and after the intervention.